An Afrocentric approach to peer mentoring in a decolonised curriculum for first-year Clinical Associate students at the University of Pretoria - Wolvaardt, Jacqueline Elizabeth (Liz) (University of Pretoria, 2024)
Thesis (PhD (Public Health: Medical Education))--University of Pretoria, 2023.